2023
DOI: 10.3390/ani13030535
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Black Cumin Seed (Nigella sativa) and Coconut Meals (Cocos nucifera) on Broiler Performance and Cecal Microbiota

Abstract: The objective of this study was to investigate the effect of dietary supplementation with black cumin seed meal (BCSM) and coconut meal (CM) on the performance and cecal microbiota of Cobb 500 hybrid broilers. The study was conducted on 600 chicks on the first day of hatching; the chicks were randomly distributed equally into 12 equal-sized floor pens. Four dietary treatments (C, T1, T2 and T3) were replicated three times (50 chicks/replicate): C was the control group; T1 was supplemented with 10% BCSM; T2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Flavonoids may be, which has a similar structure to steroid hormones, that stimulate the secretion of gonadotropin-releasing hormones, the most important of which are FSH (Follicle Stiulating Hormone) and LH (Luteinizing Hormone), which works to increase the stimulation of egg production [17]. Zaazaa et al [18] indicated that black seed contains protein of good quality, by containing essential amino acids, the most important of which is methionine, which plays a big role in increasing the size of eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Flavonoids may be, which has a similar structure to steroid hormones, that stimulate the secretion of gonadotropin-releasing hormones, the most important of which are FSH (Follicle Stiulating Hormone) and LH (Luteinizing Hormone), which works to increase the stimulation of egg production [17]. Zaazaa et al [18] indicated that black seed contains protein of good quality, by containing essential amino acids, the most important of which is methionine, which plays a big role in increasing the size of eggs.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Yesuf et al, 2023, demonestrated adding of some medicinal planst such as black cumin, fenugreek and turmerik in Cobb 500 broiler chickens diet have a significant effect on feed convertion ratio, body weight gain, and final body weights (P<0.05). Another researcher reported that, fed of broiler chickens with diets which were supplemented with different levels of cumin meal and çopra or cocount mel significantly improwed body weigh and feed conversion ratio (Zaazaa et al, 2023) (P<0.05). Our study results are inconsistent with some study results and it seems that, this difference is due to the level of medical and aromatic plants used in feed or their particle size.…”
Section: Meat Physical Analysesmentioning
confidence: 99%
“…The nutritional value and sensory quality of foods are signifi cantly aff ected by food oxidation due to the formation of ketones, quinones, phenols, carboxylic acids, aldehydes, and anhydrides that cause unpleasant taste [26]. Cumin seeds contain important valuable functional nutrients like protein, minerals, dietary fi ber, and phytochemicals [27]. Black cumin (Nigella sativa) also contains high nutritional value, minerals, protein, and soluble sugar content [20].…”
Section: Nutrients Present In Cumin Seedsmentioning
confidence: 99%